THE INFLUENCE OF AMERICAN DREAM TO THE CHARACTERIZATION OF WILLY LOMANâS IN ARTHUR MILLERâS NOVEL - Arif, Muh (Jurnal Ilmiah Administrasita, 2014)
This research aims at describing the influence of American Dream on Willy Lomanâs characterization as a husband, father, and a salesman. The research applied a library research to collect information about the Death of a Salesman,  American Dream  and the author,  Arthur  Miller In doing the analysis, the writer  used the structural  method  and sociological  approach. The data were analyzed the characterization  of  Willy  Loman  by using structural  approach,  the  writer continued  her  analysis  to  find out the influence of American Dream on Willy Lomanâs  characterizations  by using sociological  approach. The result of the research shows that Willy Lomanâs characterizations are influenced   by his ambition to pursue his American Dream. Willy  Lomanâs  dream  for  being  successful salesman and  as  a  father  makes  him  disappointed  after  he  knows  that  he  is  fired from  Howardâs  Company  and  when  he  realizes  that  Biff  in 34 years   old   does  not has  a proper  job  with  a big  salary.  The realities make Willy Loman   feels that he has failure in his life